ANTAGONISM IS THE PREDOMINANT EFFECT OF HERBICIDE MIXTURES USED FOR IMIDAZOLINONE-RESISTANT BARNYARDGRASS (Echinochloa crus-galli) CONTROL - MATZENBACHER,F. O. (2015)
ABSTRACTHerbicides mixtures are used in many situations without the adequate knowledge related with the effect on major target weeds. The objective of this study was to evaluate the effects of different herbicides mixtures used in irrigated rice in order to establish the adequate combinations for the prevention and management of herbicide resistance in barnyardgrass (Echinochloa crus-galli). Three experiments were performed at field conditions with all major post-emergent herbicides used in irrigated rice in Brazil. The first experiment was performed with barnyardgrass resistant to imidazolinone herbicides and herbicides applied at label rates. The second and third experiments were performed with barnyardgrass resistant and susceptible to imidazolinone herbicides applied at doses of 50 or 75% of the label rates. The occurrence of additive, synergistic and antagonistic effects was identified at 18, 18 and 64%, respectively, among the total of 50 different associations of herbicide and rates evaluated. In general, the mixture of ACCase inhibitors with ALS inhibitors, quinclorac, clomazone + propanil or thiobencarb resulted in antagonism. Sinergic mixtures were found in clomazone with propanil + thiobencarb, profoxydim with cyhalofop-butyl or clomazone, and quinclorac with imazapyr + imazapic, bispyribac-sodium or cyhalofop-butyl. The mixtures of quinclorac with profoxydim were antagonic. Rice grain yield varied according to the efficiency of weed control. Seveveral mixtures were effective for imidazolinone resistant barnyardgrass control.